2016
DOI: 10.15421/011609
|View full text |Cite
|
Sign up to set email alerts
|

Ecogeographical determinants of the ecological niche of the common milkweed (Asclepias syriaca) on the basis of indices of remote sensing of land images

Abstract: The patterns of variation in vegetative indices received by means of data of remote land sensing are described as being dependant on geomorphological predictors and the sizes of agricultural fields in an experimental polygon within Poltava region. The possibilities of application of vegetative indices have been explored through ecogeographical determinants of the ecological niche of the common milkweed (Asclepias syriaca L.) and other weeds. On the basis of images of the land surface taken on 23 March and 27 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
6
0
3
Order By: Relevance
“…High frequency yield components may have the character of noise and may have environmental origins as a consequence of such phenomena as the impact of diseases and pests, or the impact of weather anomalies. Changes in the abundance of pests depends on the characteris-tics of landscape diversity (Zhukov et al, 2015;Kunah, & Papka, 2016a). Analysis of the yield of grain and leguminous crops in Poltava region showed that the trend of the temporal dynamics is associated with the effect of systematic factors of an agroeconomic and agrotechnological nature .…”
Section: Discussionmentioning
confidence: 99%
“…High frequency yield components may have the character of noise and may have environmental origins as a consequence of such phenomena as the impact of diseases and pests, or the impact of weather anomalies. Changes in the abundance of pests depends on the characteris-tics of landscape diversity (Zhukov et al, 2015;Kunah, & Papka, 2016a). Analysis of the yield of grain and leguminous crops in Poltava region showed that the trend of the temporal dynamics is associated with the effect of systematic factors of an agroeconomic and agrotechnological nature .…”
Section: Discussionmentioning
confidence: 99%
“…Two groups of data were considered as ecogeographic predictors. The first group includes the digital elevation model (DEM) and its derivatives 5 . The second group includes a set of vegetation indices derived from the Landsat 8 satellite image 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Концепція топографічного індексу вологості (Topographic wetness index -TWI) уперше була запропонована К. Бівеном та Н. Кіркбі (Beven & Kirkby, 1979). Топографічний індекс вологості обчислюється за формулою TWI = ln(a/tanβ), де a -дренажна площа (площа водозбору, розрахована на одиницю довжини замикаючого контуру); β -крутість схилу (Moore, Gessler, et al, 1993;Kunah & Papka, 2016a;Zhukov & Andryushchenko, 2017).…”
Section: матеріал і методи дослідженьunclassified